Comparison of jump-landing protocols with Biodex Balance System as measures of dynamic postural stability in athletes - Krkeljas, Zarko (Taylor & Francis, 2018)
The objective of the study was to determine whether a relationship exists between the two common methods for assessing postural stability in athletes: the time-to-stabilisation (TTS) via force-plate and the Biodex Balance System (BBS). The conditions under which these measurements assess dynamic postural control may not provide sufficient feedback to practitioners. Fourty-four amateur soccer players with no history of musculoskeletal disorders volunteered for the study. Pearson correlation was used to compare the anterior-posterior (AP), medio-lateral (ML), and the overall stability indexes measured by BBS, with the corresponding parameters of TTS assessed via force plate. There was no significant correlation between any parameters of dynamic stability measured by force-plate and the stability indexes. However, there was a significant correlation between the resulting vectors and the AP component of TTS for each jump protocol. Furthermore, forward drop landing exhibited shortest TTS in AP direction, while lateral drop landing resulted in longer ML TTS relative to both forward jumps (p < 0.001). These results demonstrate that the TTS and BBS stability indexes should be used as distinct measures of dynamic postural stability. TTS protocols may be modified to target a specific training conditions or athletic population
Keywords: Time-to-stability; Biodex; Force-plate; Soccer